Characteristics of bovine muscle satellite cell from different breeds for efficient production of cultured meat - Yun-a Kim; Sehyuk Oh; Gyutae Park; Sanghun Park; Yunhwan Park; Hyunsoo Choi; Minjung Kim; Jungseok Choi (Journal of Animal Science and Technology)
The purpose of this study was comparing in vitro performances of three breeds of donor satellite cells for cultured meat and selecting the optimal donor and providing insight into the selection of donors for cultured meat production. Cattle muscle satellite cells were isolated from the muscle tissue of Hanwoo, Holstein, and Jeju black cattle, and then sorted by fluorescence activated cell sorting (FACS). Regarding proliferation of satellite cells, all three breeds showed similar trends. The myogenic potential, based on PAX7 and MYOD mRNA expression levels, was similar or significantly higher for Holstein than other breeds. When the area, width, and fusion index of the myotube were calculated through immunofluorescence staining of myosin, it was expressed upward for Holstein in all experiments except myotube area at passage 8. In addition, it was confirmed that Holstein’s muscle satellite cells showed an upward expression in the amount of gene and protein expression related to myogenic. In the case of gene expression of MYOG, DES, and MYH4 known to play a key role in differentiation into muscles, it was confirmed that Holstein’s muscle satellite cells expressed higher levels. CAV3, IGF1 and TNNT1, which contribute to hypertrophy and differentiation of muscle cells, showed high expression in Holstein. Our results suggest using cells from Holstein cattle can increase the efficiency of cultured meat production, compared to Hanwoo and Jeju breeds, because the cells exhibit superior differentiation behavior which would lead to greater yields during the maturation phase of bioprocessing.